TANGGAPAN PENGUNJUNG DALAM PENERAPAN PENGETAHUAN DAN KETERAMPILAN PEMANDU WISATA DI DESTINASI WISATA ISTANA ASSERAYAH AL-HASYIMIYAH KABUPATEN SIAK - Siregar, Ikhtiara Amwan Nisa Br.; Sidiq, Rd. Siti Sofro (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study analyzes visitor responses to the competencies of tour guides at Istana Asserayah Al-Hasyimiyah. Using a quantitative method, data from 100 respondents indicate that majority rated the knowledge aspect (63%-65%) and skills aspect (60%-65%) as very good. Overall positive ratings reached 76%-79%, although 21%-25% of respondents indicated that certainaspect, such as communication and service promotion, still require improvement. These finfings suggest that the tour guide competencies align with the 2024 SKKNI Pramuwisata standards, although enhacements in some areas are needed for more optimal service. Keywords: Tour Guide Competency, SKKNI Pramuwisata, Service Promotion